Multiple subcutaneous nodules leading to a diagnosis of metastatic neuroblastoma in an infant: A case report - Dauda E Suleiman; Zainab A Adamu; Abdullahi Mohammed (International Journal of Medicine and Health Development, 2023)
Neuroblastoma is a childhood malignancy with protean clinical manifestations. One rare presentation is multiple cutaneous nodules, especially in infants. We present a case of multiple cutaneous nodules as the initial presentation in an infant with metastatic neuroblastoma. The patient received chemotherapy with good response and is alive and well 5 years post diagnosis.